Dystonia‐deafness syndrome caused by a β‐actin gene mutation and response to deep brain stimulation. Issue 1 (8th November 2016) - Eggink, Hendriekje; van Egmond, Martje E.; Verschuuren‐Bemelmans, Corien C.; Schönherr, Marleen C.; de Koning, Tom J.; Oterdoom, D.L. Marinus; van Dijk, J. Marc C.; Tijssen, Marina A.J.
ABSTRACT: Introduction: Dystonia‐deafness syndrome is a distinct clinical presentation within the dystonia‐spectrum. Although several genetic and acquired causes have been reported, etiology remains unknown in the majority of patients. Objectives: To describe two patients with dystonia‐deafness syndrome due to a beta‐actin gene mutation. Methods: We report on disease course, genetic testing, and management of 2 patients, mother and daughter, presenting with dystonia‐deafness syndrome. Results: After exclusion of known dystonia‐deafness syndrome causes, whole‐exome sequencing revealed a beta‐actin gene mutation (p.Arg183Trp) in both patients. Although beta‐actin gene mutations are generally associated with developmental Baraitser‐Winter syndrome, dystonia‐deafness syndrome has been reported once in identical twin brothers. Bilateral GPi‐DBS led to a significant decrease of dystonia and regain of independency in our patients. Conclusion: The p.Arg183Trp mutation in the beta‐actin gene is associated with the clinical presentation of dystonia‐deafness syndrome, even with only minimal or no developmental abnormalities of Baraitser‐Winter syndrome. GPi‐DBS should be considered to ameliorate the invalidating dystonia in these patients. © 2016 International Parkinson and Movement Disorder Society.